PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN (STUDI ORENZTAXI DI SURABAYA) - Noerchoidah Noerchoidah (BISMA (Bisnis dan Manajemen), 2018)
Purpose of this study for examine and analyze the influence of the quality of service that consists of physical evidence, reliability, responsiveness, assurance and empathy for customers satisfaction Orenztaxi. This study used a quantitative research using surveys and questionnaires to 100 Orenztaxi customers in Surabaya. The data analysis technique used in this study is multiple linear regression analysis. It was found that the variable quality of services consisting of physical evidence, reliability, responsiveness, assurance, and empathy simultaneously have an influence on customers satisfaction at Orenztaxi Surabaya and the variable quality of services consisting of physical evidence, reliability, responsiveness, assurance, and empathy partially positive and significant effect on customers satisfaction at Orienztaxi Surabaya.